Study on the performance and mechanism of cementitious materials prepared by modification of sand washed filter cake on cured residual soil - Chen, Jiaxuan; Jian, Shouwei; Fan, Lulu; Tu, Liangliang; Dai, Fei; Huang, Jianxiang; Gao, Xin; Peng, Bo; He, Xinxin (Construction & building materials, 2024)
In recent years, with the rapid development of China's Shenzhen and other areas, a large number of sand washed filter cake and engineering residue soil production has exacerbated the waste of resources and environmental pressure. In order to solve the problem of sand washed filter cake and engineering residue soil treatment at the same time, to realize the "waste into treasure". This study subjects sand washed filter cake (WFC) to high-temperature modification and then uses it in conjunction with granulated blast furnace slag (GBFS) and fly ash (FA) to stabilize engineering residue soil. The performance and mechanism of the solidified soil were studied, and its economic and environmental benefits were evaluated. The results showed that the synergistic effect of modified filter cake (MFC) calcined at 750℃ with GBFS and FA effectively improved the strength of the cured soil. The best curing results were obtained with the ratio of MFC: GBFS: FA of 1:7:2, with strengths of 60 % (7d), 128 % (28d) and 234 % (90d) of the pure cement-cured soil (blank group), respectively. Meanwhile, the pore solution pH and conductivity were analyzed and found to be positively correlated with the strength of the consolidated soil. TG, SEM-EDS and other microscopic tests showed that samples of pure cement cured soil mainly generated C-S-H gels and Ettringite filled in the pores between soil particles. However, the samples of MGF cured soil, in addition to the above hydration products, a dendritic C-A-S-H gel with special morphology was also formed, which played a key role in the later strength growth of the soil. Furthermore, the cost per unit of strength and carbon emission per unit of strength can be reduced by up to 71.8 % and 88.1 %, respectively, compared with pure cement cured soil. This study provides an efficient, economical and environmentally friendly solution for the treatment of sand washed filter cake and engineering residue soil, and provides a theoretical foundation and practical guidance for further research and application of solidified soil materials. •The curing agent prepared by MFC- GBFS -FA can effectively solidify engineering residue soil.•The strength, drying shrinkage, pore solution pH and conductivity of cured soil were effectively improved.•A dendritic gel that enhances the later performance of cured soil was identified.•Environmental and economic benefits were assessed.